Treatment of recurrent or persistent spontaneous pneumothorax in children with synthetic glue pleurodesis - Vivian Ma; Ravjot Dhatt; Candace Haddock; Erik D. Skarsgard; Manraj K.S. Heran (Elsevier, 2019)
Background/purpose: The optimal treatment of recurrent pneumothorax or persistent air leak after standard surgical treatment of spontaneous pneumothorax in children is poorly defined. This study reports a preliminary experience with synthetic glue pleurodesis as definitive treatment for recurrent or refractory spontaneous pneumothorax (RPSP) in children. Methods: A retrospective review of two cases of RPSP in children treated with synthetic glue using an image-guided interventional delivery system was performed. Results: Two males (ages 13 and 16) with twice recurrent SP after video-assisted thoracic surgery (VATS) were reviewed. Both patients were treated with a radiologically-guided catheter application of synthetic glue to the presumed site of air-leak on the visceral pleural surface of the lung. Pneumothoraces resolved within 24 hours in both patients, and there have been no recurrences at a median of 12 months follow-up. Conclusions: Synthetic glue pleurodesis shows early therapeutic promise for RPSP in children, as a salvage therapy after previous VATS. Keywords: Pediatric, Spontaneous pneumothorax, Recurrent, Refractory, Glue, Pleurodesis